Peran Media Pembelajaran Dalam Meningkatkan Hasil Belajar Siswa Slow Learner - Bintang, Jasmine Mutiara; Kusuma, Karistya Tirta; Nugraha, Krisna Wahyu (Tarbi: Jurnal Ilmiah Mahasiswa, 2024)
This study explores the role that learning media plays in improving the learning outcomes of students with learning difficulties or so-called slow learners. The research was created to identify different types of media that can be used and are effective in assisting slow learners in achieving their full learning potential. The method used in this study is qualitative by collecting data from several available sources. The findings indicate that the use of learning media can provide visual and auditive stimulus that helps slow learner students understand learning materials well.